Developing A Hybrid Visual Perception Game Using The ADDIE Approach For Autism - Mohd Noor, Helmy Adly; Shahbodin, Faaizah; Che Pee @ Che Hanapi, Ahmad Naim; Yusof, Nur Fadiah; Yusoff, Marianna; Khoo, Linda Mei Sui; Kamaruzaman, Jusoff (AJBAS, 2013)
Vision problem are frequently associated with autism. Currently, a systematic diagnosed has been developed to assessing visual perception problem for autism children. However, the method for diagnosed is still by using manual and hands on technique. A systematic research framework is important in order to obtain better understanding of development a prototype. In this paper, we present a systematic research framework for hybrid diagnose and assessing visual perception problems for autism children by using serious digital game as a guide and reference to build a prototype. This research framework will be a technological solution to address visual perception problems and may benefit from intervention to improve perceptual skills among autism children. This research and invention can be used for educational area and medical field